Prognostic value of postoperative anti-thyroglobulin antibody in patients with differentiated thyroid cancer - Zhao, Yihan; Mu, Zhuanzhuan; Liang, Dongquan; Zhang, Teng; Zhang, Xin; Sun, Di; Sun, Yuqing; Liang, Jun; Lin, Yansong (Frontiers in Endocrinology, 2024)
Purpose Postoperative thyroglobulin(Tg) generally serves as a biomarker to monitor the recurrence or persistence of differentiated thyroid cancer(DTC),whereas it constrains to interference from antithyroglobulin antibody(TgAb). This study aimed to determine the value of postoperative TgAb as a surrogate for monitoring tumor status in DTCs with positive TgAb after successful RAI remnant ablation.We retrospectively enrolled DTC patients with positive(≥40 IU/mL,Roche) postoperative TgAb measurements.An index of TgAb change(∆TgAb) was defined to describe the TgAb decrease rate.DTC status was defined as either no evidence of disease(NED) or persistent/recurrent disease (PRD).Univariate and multivariate binary logistic analyses were used to identify independent risk factors of PRD.Receiver-operating characteristic(ROC) curves were performed to determine optimal cut-off values of each risk factor,and DeLong's test was conducted to compare their predictive powers.The Kaplan-Meier curves were used to assess the impact of different TgAb trends in the first year on PFS.Of the 232 patients enrolled, the median diagnosis age was 34 years(range,18-62 years),with a male to female ratio as 1:4.66(41/191).Among which, after a median follow-up of 44 months(range,4-128 months),183(78.87%) patients were evaluated as NED while the other 49(21.12%) had either persistent(n=25) or recurrent disease(n=24). Multivariate regression showed that ∆TgAb(P<0.001) and lymph node metastasis(LNM) rate(P=0.009) were independently relevant to the presence of PRD,with optimal cut-off values of 47.0% and 35.1%, respectively.Of note,there is a high negative predictive value of ∆TgAb with the cut-off of 47.0%.DeLong's test showed that ∆TgAb alone and the combination of ∆TgAb and LNM rate were significantly greater than isolated LNM rate(both P<0.001) in predicting NED,while there was no statistical difference of the predictive power between ∆TgAb and the combination (P=0.203). Additionally, patients with ∆TgAb>47.0% had longer progression-free survival than those with ∆TgAb≤47.0%(not reached vs. 50 months,P<0.001),and those with ∆TgAb>47.0% or negative conversion within the first year after RAI ablation had longer progression-free survival.Our study suggested ∆TgAb could serve as a valuable indicator of disease status in DTC patients with positive TgAb,a ∆TgAb of >47.0% is conducive to identify those with NED and may help to obviate their overtreatment.The decrease rate and negative conversion of TgAb in the first year were good predictors of disease-free survival in patients.